2022
DOI: 10.1089/ast.2021.0012
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Cycling and Biosignatures in a Hyperarid Mars Analog Environment

Abstract: The hyperarid Atacama Desert is a unique Mars-analog environment with a large near-surface soil nitrate reservoir due to the lack of rainfall leaching for millennia. We investigated nitrogen (N) cycling and organic matter dynamics in this nitrate-rich terrestrial environment by analyzing the concentrations and isotopic compositions of nitrate, organic C, and organic N, coupled with microbial pathway-enzyme inferences, across a naturally occurring rainfall gradient. Nitrate deposits in sites with an annual prec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 97 publications
(134 reference statements)
2
7
0
1
Order By: Relevance
“…The detection of markers related to nitrogen metabolism by SOLID-LDChip indicates how relevant this metabolism is in the sampling area, where low biomass results in nitrate metabolism and nitrogen fixation playing a pivotal role in the system as has recently been reported (Shen et al , 2021 , 2022 ). Although genes and proteins involved in nitrogen fixation have been found in hyperarid soils (Wilhelm et al , 2018 ; Fernández-Martínez et al , 2019 ; Shen et al , 2021 , 2022 ), apart from Chloroflexi, Cyanobacteria and other potential nitrogen fixers are absent or patchy present near the surface (Warren-Rhodes et al , 2019 ); therefore, inputs due to nitrogen fixation seem to play a minor role in the nitrogen cycle (Shen et al , 2022 ).…”
Section: Discussionmentioning
confidence: 81%
“…The detection of markers related to nitrogen metabolism by SOLID-LDChip indicates how relevant this metabolism is in the sampling area, where low biomass results in nitrate metabolism and nitrogen fixation playing a pivotal role in the system as has recently been reported (Shen et al , 2021 , 2022 ). Although genes and proteins involved in nitrogen fixation have been found in hyperarid soils (Wilhelm et al , 2018 ; Fernández-Martínez et al , 2019 ; Shen et al , 2021 , 2022 ), apart from Chloroflexi, Cyanobacteria and other potential nitrogen fixers are absent or patchy present near the surface (Warren-Rhodes et al , 2019 ); therefore, inputs due to nitrogen fixation seem to play a minor role in the nitrogen cycle (Shen et al , 2022 ).…”
Section: Discussionmentioning
confidence: 81%
“…They suggest (Shen et al, 2021). This suggests a scenario where as Mars becomes more habitable after a warming pulse, life through denitrification makes the biosphere more habitable for nitrogen fixing photosynthetic life, which would strengthen the Swansong Gaia effect, with the CO₂ removed more rapidly the thicker the atmosphere.…”
Section: Primary Conclusion Are As Followsmentioning
confidence: 99%
“…• Microbes from near the surface in Jezero crater would withstand temperatures varying from below -70 °C to above 15 °C in a single dayand major changes in humidity and pressurethis is likely to favour polyextremophilesand martian life would likely be able to resist higher levels of stresses like UV, low humidity, vacuum, desiccation, and ionizing radiationand may be able to fix nitrogen at low concentrationswhich seems likely to make it easier not harder for them to survive on Earth if Mars life behaves like life in Mars analogue deserts a complex picture of denitrification / nitrogen fixation arises (Shen et al, 2021) which reinforces the Swansong Gaia effect.…”
Section: Primary Conclusion Are As Followsmentioning
confidence: 99%
See 1 more Smart Citation
“…Metagenomics studies on the halite microbiome in the Atacama have shown a limited genetic repository for sulfate oxidation but the presence of genes of all the enzymes involved in the assimilatory sulfate reduction pathway, with direct implication on sulfate uptake from oceanic fog, amino acid biosynthesis, microbial metabolism, and sulfur cycle (Gómez-Silva, 2010 ; Gómez-Silva et al, 2019 ). Also, active metabolic capabilities such as photosynthetic and transcriptional activities have been demonstrated in microbial consortia inhabiting halites and wetlands, and nitrogen cycling along the rainfall gradient in the Atacama (Davila et al, 2015 ; Orellana et al, 2020 ; Uritskiy et al, 2020 ; Castro-Severyn et al, 2021 ; Shen et al, 2021b ). New questions and ingenious experimental approaches are needed to produce comprehensive knowledge about the role of microbes in biogeochemical cycles, the cellular bases that assist the crosstalk between microbial cells, the trans-kingdom molecular mechanisms playing key roles in the gene expression dynamic, among other topics not covered to date.…”
Section: Bases For a New View Of The Atacama Desertmentioning
confidence: 99%